2022
DOI: 10.3390/cimb44050151
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic Effect of Ascorbic Acid and Resveratrol in Erythrocytes of Ambystoma mexicanum, Oreochromis niloticus and Human Lymphocytes Exposed to Glyphosate

Abstract: Glyphosate is a controversial herbicide. Its genotoxicity and presence in various ecosystems have been reported. The use of ascorbic acid and resveratrol could protect different organisms from glyphosate-induced genetic damage. In the present study, specific genetic damage induced by glyphosate was evaluated in erythrocytes of Oreochromis niloticus, Ambystoma mexicanum and human lymphocytes. Simultaneously, the antigenotoxic capacity of various concentrations of ascorbic acid and resveratrol was evaluated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Although there is evidence of the genotoxic activity of G [7,8], this is controversial [16,18], and it is necessary to increase the degree of certainty of its genotoxicity. Alvarez-Moya et al [34] reported the genotoxicity of G in the blood of humans in a mean concentration of 0.0007-0.7 mM. To ensure the analysis of genotoxic activity, high concentrations (50 and 10 mM) and lower ones such as those reported by Khan et al [7] were used, observing the dose-dependent genotoxic activity of G, from 0.1 mM-50 mM, using the tail length, tail moment, and MG parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is evidence of the genotoxic activity of G [7,8], this is controversial [16,18], and it is necessary to increase the degree of certainty of its genotoxicity. Alvarez-Moya et al [34] reported the genotoxicity of G in the blood of humans in a mean concentration of 0.0007-0.7 mM. To ensure the analysis of genotoxic activity, high concentrations (50 and 10 mM) and lower ones such as those reported by Khan et al [7] were used, observing the dose-dependent genotoxic activity of G, from 0.1 mM-50 mM, using the tail length, tail moment, and MG parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline comet assay was carried out using the method of Speit and Hartm [45], as was mentioned by Alvarez-Moya et al [34]. It is as follows: slides were cov with Normal Melting Point (NMP) agarose at 1%, then the agarose was allowed to ify, and then it was removed from the slides, giving a completely clean surface as a r Next, a 0.6% Low Melting Point (LMP) agarose layer was placed on each slide.…”
Section: Comet Assaymentioning
confidence: 99%
“…It is pertinent to mention that Oreochromis niloticus erythrocytes and human and mouse lymphocytes have been used as biomonitors of genetic damage induced by pesticides (Alvarez-Moya et al, 2022).…”
Section: Issn Online 2007-9621mentioning
confidence: 99%
“…A paper published by Alvarez-Moya et al in 2022 showed conclusively that glyphosate is genotoxic to erythrocytes of salamanders and tilapia, as well as human lymphocytes. They also showed that supplementation with ascorbate and resveratrol (an antioxidant) reduced glyphosate's genotoxic effects [30].…”
Section: Introductionmentioning
confidence: 99%